Closure of a Recurrent Bronchopleural Fistula Using a Matrix Seeded With Patient‐Derived Mesenchymal Stem Cells. (24th June 2016) - Aho, Johnathon M.; Dietz, Allan B.; Radel, Darcie J.; Butler, Greg W.; Thomas, Mathew; Nelson, Timothy J.; Carlsen, Brian T.; Cassivi, Stephen D.; Resch, Zachary T.; Faubion, William A.; Wigle, Dennis A.
Abstract : Management of recurrent bronchopleural fistula (BPF) after pneumonectomy remains a challenge. Although a variety of devices and techniques have been described, definitive management usually involves closure of the fistula tract through surgical intervention. Standard surgical approaches for BPF incur significant morbidity and mortality and are not reliably or uniformly successful. We describe the first‐in‐human application of an autologous mesenchymal stem cell (MSC)‐seeded matrix graft to repair a multiply recurrent postpneumonectomy BPF. Adipose‐derived MSCs were isolated from patient abdominal adipose tissue, expanded, and seeded onto bio‐absorbable mesh, which was surgically implanted at the site of BPF. Clinical follow‐up and postprocedural radiological and bronchoscopic imaging were performed to ensure BPF closure, and in vitro stemness characterization of patient‐specific MSCs was performed. The patient remained clinically asymptomatic without evidence of recurrence on bronchoscopy at 3 months, computed tomographic imaging at 16 months, and clinical follow‐up of 1.5 years. There is no evidence of malignant degeneration of MSC populations in situ, and the patient‐derived MSCs were capable of differentiating into adipocytes, chondrocytes, and osteocytes using established protocols. Isolation and expansion of autologous MSCs derived from patients in a malnourished, deconditioned state is possible. Successful closure and safety data for this approach suggest the potential for an expanded study of the role of autologous MSCs in regenerative surgical applications for BPF. Significance: Bronchopleural fistula is a severe complication of pulmonary resection. Current management is not reliably successful. This work describes the first‐in‐human application of an autologous mesenchymal stem cell (MSC)‐seeded matrix graft to the repair of a large, multiply recurrent postpneumonectomy BPF. Clinical follow‐up of 1.5 years without recurrence suggests initial safety and feasibility of this approach. Further assessment of MSC grafts in these difficult clinical scenarios requires expanded study. Abstract : This is the first‐in‐human application of an autologous mesenchymal stem cell (MSC)‐seeded matrix graft to repair a multiply recurrent postpneumonectomy bronchopleural fistula (BPF). Adipose‐derived MSCs were isolated from patient abdominal adipose tissue, expanded, and seeded onto bio‐absorbable mesh, which was surgically implanted at the BPF site. After clinical follow‐up of 1.5 years, the patient is clinically asymptomatic without evidence of recurrence or malignant degeneration of MSC populations in situ.